Studi Kasus : Asuhan Keperawatan Menyusui Tidak Efektif Pada Postpartum dengan Terapi Pijat Laktasi : Case Study: Ineffective Nursing Care for Breastfeeding in Postpartum with Lactation Massage Therapy - Intan Nurlaila; Dwining Handayani; R.A. Helda Puspitasari; Bagus Dwi Cahyono (Journal of Nursing Education and Practice, 2026)
Introduction: The postpartum period is a critical phase for mothers in providing optimal nutrition through breastfeeding. However, ineffective breastfeeding remains a common problem, characterized by inadequate milk production, poor infant attachment, maternal anxiety, fatigue, and difficulties in positioning the infant during feeding. These conditions may interfere with successful breastfeeding and reduce maternal confidence. Lactation massage is a nonpharmacological intervention that may stimulate oxytocin secretion, enhance milk flow, and improve breastfeeding effectiveness.Objective: This study aimed to describe the implementation of nursing care using lactation massage therapy in a postpartum patient experiencing ineffective breastfeeding.Method: This study employed a case study approach involving one postpartum patient diagnosed with ineffective breastfeeding at RSUD dr. R. Soedarsono Pasuruan. Data were collected through interviews, observation, physical examination, and documentation. Nursing interventions included breastfeeding education and lactation massage therapy applied to the neck, shoulders, scapula, back, and breast areas for 15–20 minutes daily over three consecutive days. Evaluation focused on breastfeeding effectiveness indicators, including milk flow, infant attachment, maternal positioning during breastfeeding, infant urination frequency, sucking strength, maternal comfort, and confidence.Result: Following three days of intervention, improvements were observed in several indicators of breastfeeding effectiveness. Breast milk flow became smoother, infant attachment and positioning improved, sucking strength increased, and infant urination frequency rose from five to nine times per day. In addition, maternal anxiety and fatigue decreased, while comfort and confidence in breastfeeding improved. By the third day, the nursing problem of ineffective breastfeeding was considered resolved.Conclusion: Lactation massage combined with breastfeeding education was associated with improved breastfeeding effectiveness in this postpartum patient. This intervention may be considered a supportive nonpharmacological nursing strategy to promote successful breastfeeding and maternal well-being during the postpartum period.